Increased algicidal activity of Aeromonas veronii in response to Microcystis aeruginosa: interspecies crosstalk and secondary metabolites synergism. (13th March 2019) - Weiss, Gad; Kovalerchick, Dimitry; Lieman‐Hurwitz, Judy; Murik, Omer; De Philippis, Roberto; Carmeli, Shmuel; Sukenik, Assaf; Kaplan, Aaron
Summary: Toxic Microcystis spp. blooms constitute a serious threat to water quality worldwide. Aeromonas veronii was isolated from Microcystis sp. colonies collected in Lake Kinneret. Spent Aeromonas media inhibits the growth of Microcystis aeruginosa MGK isolated from Lake Kinneret. The inhibition was much stronger when Aeromonas growth medium contained spent media from MGK suggesting that Aeromonas recognized its presence and produced secondary metabolites that inhibit Microcystis growth. Fractionations of the crude extract and analyses of the active fractions identified several secondary metabolites including lumichrome in Aeromonas media. Application of lumichrome at concentrations as low as 4 nM severely inhibited Microcystis growth. Inactivation of avi H in the lumichrome biosynthetic pathway altered the lumichrome level in Aeromonas and the extent of MGK growth inhibition. Conversely, the initial lag in Aeromonas growth was significantly longer when provided with Microcystis spent media but Aeromonas was able to resume normal growth. The longer was pre‐exposure to Microcystis spent media the shorter was the lag phase in Aeromonas growth indicating the presence of, and acclimation to, secondary MGK metabolite(s) the nature of which was not revealed. Our study may help to control toxic Microcystis blooms taking advantage of chemical languages used in the interspecies communication.